UPDATING MECH ANISMS FO R DIGITALIZATION OF COOPERATION IN THE ECONOMIC SPACE OF THE EURASIAN ECONOMIC UNION - Osnovin, Sergey; Malicevic, Natalia; Malicevic, Ilya (Економічний дискурс, 2020)
Introduction. Currently, the EEU countries have the task of conducting digital transformation, so that all sectors of the real economy are comparable to those of the world's giants. Digital transformation of industry the transition of the industrial sector from one technological structure to another in order to increase productivity and profitability. The digital spaces of countries are heterogeneous, s o each country creates its own digital space. Results. The article contains materials on the digital space of the Eurasian Economic Union, which is being formed for the integration of the EEU countries. The article describes the parameters of digital trans formation of industry, which is carried out using the Eurasian digital platform and the services of the integrated information system of the Union in cooperation with the Eurasian network: industrial cooperation, technology transfer and technology platform s. Methods. The methodological basis of the research was the work of leading scientists on updating the mechanisms of digitalization of cooperation in the economic space of the EEU in order to study the parameters of industrial transformation taking into a ccount the global challenges of digital transformation. The methodological basis of the study is formed by the general scientific principles of a systematic approach; analysis methods logical, comparative, strategic, managerial and others. Discussion. Th erefore, focusing on the goals of digital transformation of industry, we recommend: creating a system for evaluating and rating organizations; identifying systemic problems; implementing best practices and digital industrial technologies; establishing coop eration with third countries; identifying financial instruments to encourage the introduction of digital platforms in industry; stimulating interaction between business communities of member States; creating a system for cataloging industrial products of member states.